Caseous Lymphadenitis (CLA) Cases in Boer Goats - Elok Sukma Pertiwi; Nenny Harijani; Iwan Sahrial Hamid; Widya Paramita Lokapirnasari (Journal of Applied Veterinary Science And Technology, 2020)
Background: Caseous lymphadenitis (CLA) is a chronic infectious bacterial disease of sheep and goats caused by corynebacterium pseudotuberculosis. Purpose: To determine the percentage of cases and procedures for treating Caseous lymphadenitis in Boer goats in Edufarm Kambing Burja. Methods: Data obtained from observations of 120 Boer goats and interviews with livestock owners. The data obtained were analyzed according to the reference literature. Result: The percentage of Caseous lymphadenitis in Boer goats was 8.33%. Conclusion: Procedure for handling and controlling Caseous lymphadenitis in Boer goats using abscess drainage procedures and vaccination.